2020
DOI: 10.1002/ajp.23222
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Injurious behavior in rhesus macaques: Issues and challenges

Abstract: Some monkeys housed in research facilities develop abnormal behavior ranging from stereotypic to the more serious condition of self-injurious behavior (SIB).We initially sought to understand how and why monkeys engaged in SIB and more importantly why only a small percentage of laboratory monkeys, with seemingly similar housing and background, developed this disorder. Of particular importance was the recognition that different pathways might lead to SIB and that strong individual differences would affect the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
5
0
1
Order By: Relevance
“…A behavior in which an individual either causes, or has the potential to cause, a self‐inflicted injury that may require veterinary care; however, actual injury is relatively rare (Anderson & Chamove, 1980; C. Lutz et al, 2003; M. A. Novak, 2003; M. A. Novak, 2020). Examples of SIB include head banging, self‐biting, self‐hitting/slapping, and wounding due to aggressive hair plucking, and excessive wound picking (Bauer & Baker, 2016; Crast et al, 2014; Gottlieb, Capitanio, et al, 2013; Hosey & Skyner, 2007; C. K. Lutz, 2018; C. Lutz et al, 2003; Rommeck, Anderson, et al, 2009), with wounding severity differing markedly across individuals (Z. T. Freeman, Krall, et al, 2015; M. A. Novak, 2020).…”
Section: Classification and Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…A behavior in which an individual either causes, or has the potential to cause, a self‐inflicted injury that may require veterinary care; however, actual injury is relatively rare (Anderson & Chamove, 1980; C. Lutz et al, 2003; M. A. Novak, 2003; M. A. Novak, 2020). Examples of SIB include head banging, self‐biting, self‐hitting/slapping, and wounding due to aggressive hair plucking, and excessive wound picking (Bauer & Baker, 2016; Crast et al, 2014; Gottlieb, Capitanio, et al, 2013; Hosey & Skyner, 2007; C. K. Lutz, 2018; C. Lutz et al, 2003; Rommeck, Anderson, et al, 2009), with wounding severity differing markedly across individuals (Z. T. Freeman, Krall, et al, 2015; M. A. Novak, 2020).…”
Section: Classification and Identificationmentioning
confidence: 99%
“…Animals often resume the abnormal behavior after they have become habituated to the enrichment (in the case of toys) or after it has served its purpose (i.e., there is no more food present in the case of a puzzle ball). Further, while relatively useful for treating abnormal repetitive behaviors, at least in the short term, enrichment is less effective as a treatment for SIB (Novak et al, 1998; see also M. A. Novak, 2020).…”
Section: Treatment Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagner et al observed the behavior of capuchin monkeys in the public Zoo of Vers-Duifen, Brazil, for 40 days to determine the frequency of stereotypical behavior and self-orientation and to analyze the effects on behavioral stability [12]. In addition to zoos, the stereotypical behavior of monkeys in research facilities was observed and analyzed [13]. These observations and analyses were made by looking at video recordings of animal behavior and then analyzing them.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for evaluating the rhesus monkey model of SIB is based, in part, on disturbing trends showing that NSSI is on the rise among teenagers and young adults ( Wester et al, 2018 ) and on significant animal welfare concerns for non-human primates with this condition ( Novak, 2020 ). Humans and Old World monkeys such as rhesus macaques share many important features including a long lifespan, complex social structures, higher order cognitive processes, large brains in relation to body size, and hands adapted for manipulation of objects.…”
Section: Introductionmentioning
confidence: 99%